PERTANGGUNGJAWABAN PIDANA BAGI PELAKU POLITIK UANG DALAM PEMILIHAN UMUM DI KABUPATEN LEMBATA PROVINSI NUSA TENGGARA TIMUR - Uran, Maria Novita Nigun; Sinurat, Aksi; Wilhelmus, Bhisa Vitus (Petitum Law Journal, 2025)
This study examines the use of money politics in Lembata Regency by emphasizing the legal responsibility of the perpetrators and preventive efforts by Bawaslu, the Police, and the Prosecutor's Office. Using a descriptive-analytical approach, data were obtained through interviews with the Lembata Bawaslu Secretariat Coordinator and relevant literature reviews. The research findings indicate that the management of money politics faces various complex challenges: (1) structural obstacles such as the perpetrators' escape, weak evidence of transactions, and ineffective coordination between institutions; (2) the shift in the practice of money politics from giving cash to project-based activities or social relationships that are difficult to suspect; and (3) the powerlessness of the Gakkumdu mechanism due to its reliance on unanimous consensus and strict administrative time limits. This study shows that law enforcement is hampered by the dualism of regulations (the Criminal Code versus the Election Law) and the influence of local political interests. Some recommended solutions include increasing investigative capacity utilizing technology, devolution of prosecutorial authority, public education for participatory supervision, and adjustments to general and specific criminal laws. Without comprehensive reform, law enforcement efforts in elections risk getting caught up in procedural formalities.